2022
DOI: 10.1136/bmjopen-2021-053741
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for the evaluation of pharmacist-participated medication reconciliation at county hospitals in China: a multicentre, open-label, assessor-blinded, non-randomised, controlled study

Abstract: IntroductionPharmacist-participated medication reconciliation proved an effective strategy to decrease the risk of medication discrepancy-related errors. However, it is still under pilot in China and its effectiveness in the Chinese healthcare system remains unclear. This study aims to conduct a pharmacist-participated medication reconciliation intervention for elderly patients in county hospitals in China and to evaluate its effect.Methods and analysisThis is a multicentre, prospective, open-label, assessor-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We planned to conduct our intervention in seven county-level hospitals, but were only able to do so in six county-level hospitals, as one did not conduct the intervention as planned. Furthermore, due to the inaccessibility of the data, we could not estimate medical costs as described in the protocol [ 21 ] and were thus unable to conduct a cost-benefit analysis. Moreover, we conducted cluster-level intervention to eliminate contamination between the intervention and control group, but there might still be unpredictable leakage between colleagues at the same hospital, possibly diminishing the difference between the control and intervention groups and thus leading to an underestimation of the true effect of our intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We planned to conduct our intervention in seven county-level hospitals, but were only able to do so in six county-level hospitals, as one did not conduct the intervention as planned. Furthermore, due to the inaccessibility of the data, we could not estimate medical costs as described in the protocol [ 21 ] and were thus unable to conduct a cost-benefit analysis. Moreover, we conducted cluster-level intervention to eliminate contamination between the intervention and control group, but there might still be unpredictable leakage between colleagues at the same hospital, possibly diminishing the difference between the control and intervention groups and thus leading to an underestimation of the true effect of our intervention.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the ethical approval from the Peking University Institution Review Board (IRB00001052-21016) and all participating county-level hospitals. We performed the study and reported our findings per the CONSORT guidelines [ 19 , 20 ], registered it with the Chinese Clinical Trial Registry (ChiCTR2100045668), and published the protocol elsewhere [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“… 21 In recent years, MR is still in an experimental stage in China. 22 For the BPMH to be obtained, at least two data sources are required, which may include a patient/family/caregiver interview, an EMR medication list, a patient prescription list/pill bottles, and a discharge summary. 11 However, there is a lack of information on which sources should be prioritized.…”
Section: Introductionmentioning
confidence: 99%